COVID-19 and the teacher’s voice: self-perception and contributions of speech therapy to voice and communication during the pandemic (Clinics, 2021)
OBJECTIVES: We aimed to analyze the vocal self-perception of Brazilian teachers and their communication needs, vocal signs and symptoms, and voice-related lifestyles during the coronavirus disease (COVID-19) pandemic and, based on this information, to develop guidance materials intended for dissemination to these teachers and the general community. METHODS: An online questionnaire designed for this survey was distributed via the researchers’ networks and was available for completion by any teacher, except those who were not working at the time. There were 1,253 teachers from all over Brazil, of both sexes, covering a wide age range, working at different levels of education, and most with more than ten years of experience. Descriptive and inferential analyses of the data were performed. RESULTS: On comparing the prepandemic period with the current one, participants indicated voice improvements. In contrast, they presented symptoms such as dry throat, effort in addressing remote classes, hoarseness after classes, and difficulties with the use of headphones, among others. They further indicated stress, general fatigue, impact of the pandemic on mental health, and the overlapping of many home tasks with professional tasks. Some smoked, and others hydrated insufficiently. CONCLUSION: Although teachers generally noticed voice improvements during the pandemic, a proportion of them perceived worsening of voices. Many indicated several factors in which speech-language pathologists could guide them with the aim of improving performance and comfort during remote and hybrid classes, an initiative that will positively impact not only their voice and communication but also their quality of life.